2003
DOI: 10.1385/ir:27:1:31
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Control Mechanisms in B-1 and B-2 Lymphoid Subsets

Abstract: An effective humoral response requires that a given B lymphocyte population express a repertoire of receptors capable of recognizing a distinct array of antigens, while at the same time disregarding self-antigens. Mature B cells interacting with antigen via their B cell antigen receptors (BCRs) enter G(1) phase of the cell cycle and, depending on the strength of the signal, can commit to S phase entry. Input from co-receptors, which may function to either enhance or inhibit BCR signals, also influence the deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 127 publications
1
19
0
Order By: Relevance
“…31,32 In various cell types critical proliferative signals are transmitted through Akt, ERK, JNK, p38 MAPK and the NF-kB pathway, which have all been shown to be activated by CpG ODN stimulation. 42,[19][20][21][22] We observed that activation of these signaling molecules is stronger and/or prolonged in the proliferating CLL samples, indicating that differences in the amplitude and/or kinetics of the CpG ODN-induced signal may be responsible for the observed differences in the proliferative response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 In various cell types critical proliferative signals are transmitted through Akt, ERK, JNK, p38 MAPK and the NF-kB pathway, which have all been shown to be activated by CpG ODN stimulation. 42,[19][20][21][22] We observed that activation of these signaling molecules is stronger and/or prolonged in the proliferating CLL samples, indicating that differences in the amplitude and/or kinetics of the CpG ODN-induced signal may be responsible for the observed differences in the proliferative response.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Stimulation with CpG ODN resulted in strong induction of cyclin D3 and downregulation of p27KIP1 in 4/4 proliferating and 5/5 nonproliferating CLL B-cell samples, indicating that all CLL B-cells enter the G 1 phase of the cell cycle ( Figure 4). Cyclin D2 and p21CIP were only weakly detected and their levels did not change substantially following CpG ODN stimulation, which may reflect a nonessential role for these proteins in cell cycle regulation of CLL B-cells in this setting.…”
Section: Reduced or Absent Induction Of Cyclin E And Cyclin A In Cll mentioning
confidence: 99%
“…Targeted loss of the antiapoptotic member gene Bcl-2 has led to massive apoptosis of lymphocytes, whereas overexpression of Bcl-2 has caused the accumulation of B cells (4,5). D-type cyclins are key players in the G 1 checkpoint control mechanism and are critical for cell proliferation (6). Both Bcl-2 and D-type cyclins are prime targets for novel therapeutics because their overexpression is common in many hematological diseases and many types of cancers (7,8).…”
mentioning
confidence: 99%
“…Cell proliferation induced by engagement of the BCR and costimulatory receptors such as CD40 requires successful transition through different cell cycle phases and checkpoints (1). Upon receiving the activation signal, the decision of resting B cells to enter the cell cycle reflects a balance between growth-promoting and growth-inhibitory regulators (2). D-type cyclins are key regulators for the G 1 /S transition checkpoint and are primary targets for proliferation signals.…”
mentioning
confidence: 99%
“…D-type cyclins are key regulators for the G 1 /S transition checkpoint and are primary targets for proliferation signals. Among the three members of D cyclins, cyclin D2 is the main D-type cyclin expressed in mature mouse B cells and plays an important role in cell proliferation after BCR-mediated proliferation (2)(3)(4)(5). However, the transcriptional control of cyclin D2 expression in B cells is not completely understood.…”
mentioning
confidence: 99%